Eliminating Voltage Decay of Lithium‐Rich Li1.14Mn0.54Ni0.14Co0.14O2 Cathodes by Controlling the Electrochemical Process. Issue 20 (27th March 2015) - Wei, Zhen; Zhang, Wei; Wang, Feng; Zhang, Qian; Qiu, Bao; Han, Shaojie; Xia, Yonggao; Zhu, Yimei; Liu, Zhaoping
Abstract A lithium‐rich cathode material Li1.14Mn0.54Ni0.14Co0.14O2 (LNMCO) is prepared by a co‐precipitation method. The issue of voltage decay in long‐term cycling is largely eliminated by control of the charge–discharge voltage range. The LNMCO material exhibits 9.8 % decay in discharge voltage over 200 cycles between 2.0–4.6 V, during which the working voltage decays significantly, from 3.57 V to 3.22 V. The decay was decelerated by a factor of six by using a voltage window of 2.0–4.4 V, from 3.53 V to 3.47 V. IR and Raman spectra reveal that the transformation of layered structure to spinel is significantly retarded under 2.0–4.4 V cycling conditions. Transmission electron microscopy (TEM) was also applied for examining phase change in an individual particle during cycling, showing that the spinel phase occurs both at 2.0–4.6 V and at 2.0–4.4 V, but is not dominant in the latter. Normalization of Li can remove the additional impact on the voltage decay which is brought by different amounts of Li intercalation. The mechanism of no voltage decay at 2.0–4.4 V cycling is raised and electrochemical impedance spectrum data also support the hypothesis.